Methicillin-resistant Staphylococcus aureus screening in healthcare workers: should a new protocol be introduced? - Gurjar, Sahil; Mathur, Namami; Jadhavar, Sulochana R. (International Journal of Research in Medical Sciences, 2021)
Background: In recent times, emerging resistance to majority of antibiotic classes seen in Methicillin-resistant Staphylococcus aureus (MRSA) isolates is of concern in hospital-acquired infection. MRSA carriage by healthcare workers (HCWs) has been documented to be as high as 50% in some studies. Higher carrier rate increases the risk of developing active infection as well as transmission of infection to the patients. The study aims to establish a relationship between MRSA carrier rate and healthcare workers of a tertiary care hospital in Pune and understand the need for screening regimens, based on the outcome. Methods: A cross-sectional study including health care workers from a tertiary care hospital working in different clinical departments was carried out. Data was collected by taking samples of nasal swabs of 115 HCWs and inoculated immediately on blood agar. Culture plates were incubated at 37°C for 24 hours and colonies were tested by routine diagnostic techniques. Antibiotic sensitivity was tested using cefoxitin discs on Mueller Hinton medium. Results: Prevalence of Staphylococcus aureus carriage was reported in 19 out of 115 (16.52%) healthcare workers, of which 63.2% were MRSA and 36.8% were MSSA. Prevalence of MRSA among Orthopaedic surgeons and General surgeons showed a carrier rate of 25% and 18.2% respectively. Nurses had a prevalence rate of 0.39 %. Overall prevalence of MRSA carriage in healthcare workers was reported to be 10.4% Conclusions: MRSA carriage among HCWs at the hospital is considerably high. The high prevalence of MRSA carriage emphasizes the need for stringent hospital infection control and regular screening regimen of HCWs.